2010
DOI: 10.1021/ic100080k
|View full text |Cite
|
Sign up to set email alerts
|

Is Vanadate Reduced by Thiols under Biological Conditions? Changing the Redox Potential of V(V)/V(IV) by Complexation in Aqueous Solution

Abstract: Although dogma states that vanadate is readily reduced by glutathione, cysteine and other thiols, there are several examples documenting that vanadium(V)-sulfur complexes can form and be observed. This conundrum has impacted life scientists for more than two decades. Investigation of this problem requires an understanding of both the complexes that form from vanadium(IV) and (V) and a representative thiol in aqueous solution. The reactions of vanadate and hydrated vanadyl cation with 2-mercaptoethanol have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 106 publications
3
81
1
3
Order By: Relevance
“…Indeed, the disruption of the bridge by mutagenesis modified notably Nox4 ROS production [43]. Disulfide bridges with a standard redox potential (E 0 ) of À180 mV [47] could be reduced by NADPH, NADH and b-mercaptoethanol that possess a lower E 0 (À324, À320, and À253 mV, respectively) [48]. Our results using those reducing agents indicated that Nox4 activity could be stimulated by extracellular redox modifications, possibly through the reduction of its disulfide bridge.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, the disruption of the bridge by mutagenesis modified notably Nox4 ROS production [43]. Disulfide bridges with a standard redox potential (E 0 ) of À180 mV [47] could be reduced by NADPH, NADH and b-mercaptoethanol that possess a lower E 0 (À324, À320, and À253 mV, respectively) [48]. Our results using those reducing agents indicated that Nox4 activity could be stimulated by extracellular redox modifications, possibly through the reduction of its disulfide bridge.…”
Section: Discussionmentioning
confidence: 73%
“…Vanadium in oxidation state 5+ (V 5+ ) also can bind with thiol groups of cellular proteins and form stable complexes. 34 Furthermore, the oxidation-reduction between V 4+ and V 5+ can lead to oxidative stress of bacterial cells and improve antibacterial activity. It was not possible to conduct experiments using only the β-AgVO 3 (without AgNPs) because this hybrid material is obtained by a one-step process.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidised, active site thiols of PTPs are directly targeted by GSH, leading to enzyme reactivation. Together with the propensity of GSH to directly discourage the formation of PTPinhibitory V(V) [56,57], this may explain why BSO can generate a potent mixture with BMOV to potentially block critical members of this enzyme family.…”
Section: Apoptosis (Summarised In Supplementarymentioning
confidence: 99%